Corrigendum to ?Short lead time standard precipitation index forecasting: Extreme learning machine and variational mode decomposition? [J. Hydrol. Reg. Stud. 54 (2024) 101861] (Journal of Hydrology: Regional Studies (2024) 54, (S221458182400209X), (10.1016/j.ejrh.2024.101861)) - Ladouali S.; Katipo?lu O.M.; Bahrami M.; Kartal V.; Sakaa B.; Elshaboury N.; Keblouti M.; Chaffai H.; Salem A.; Pande C.B.; Elbeltagi A. (Elsevier B.V., 2025)
The authors regret the need to issue this corrigendum to acknowledge the change in author name and address for correspondence. 1- The author's name ?Salem Ali? should be ?Ali Salem? 2- Corresponding author at: Structural Diagnostics and Analysis Research Group, Faculty of Engineering and Information Technology, University of Pcs, Hungary We thank the journal for accommodating this update. The authors would like to apologise for any inconvenience caused. ? 2024 The Authors